Asuhan Keperawatan pada Tn. R dan Tn. M yang Mengalami Penurunan Curah Jantung dengan Gagal Jantung Kongestif di RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Anggraeni, Selva; Vestabilivy, Evi; Fatkhurrohman, Mohammad (STIKes Persada Husada Indonesia, 2024)
Congestive heart failure is defined as the inability of the heart to pump blood in sufficient quantities to meet the tissue's need for oxygen so that metabolism decreases. Based on Riskesdas data in 2018 the estimated number of heart failure sufferers was as much as 1.5% or around 29,550 people While in 2013 it was 0.5%, this shows an increase in the number of heart failure sufferers in Indonesia. This study aims to obtain an overview of the implementation of nursing care in patients with Congestive Heart Failure at dr. Chasbullah Abdulmadjid Hospital Bekasi City. Theresearch used in the preparation of this scientific paper is qualitative, descriptive, case study approach with intervention. The participants in this case were patients at dr. Chasbullah Abdulmadjid Hospital Bekasi City. The characteristics of patients who were the subjects of this study were patients who had been diagnosed with congestive heart failure and had the same nursing problem, namely decreased cardiac output. The results of the study showed complaints of tightness, coughing, fatigue during activities, edema, defecate difficulty and complaining of difficulty sleeping. Based on these data, 6 diagnoses were found in Mr. R and 5 diagnoses in Mr. M, 5 of which had similaritiessuch as decreased cardiac output, ineffective breathing patterns, hypervolemia, activity intolerance and constipation. Another diagnosis is sleep pattern disturbance. The main planning carried out on both patients is monitoring vital signs, monitoring oxygen saturation, and fluid restriction. The main nursing action performed on both patients was Semi-Fowler positioning. The evaluation obtained after treatment for 3 x 24 hours is that the decrease in cardiac output has not been resolved because both patients still complain of fatigue.